2021
DOI: 10.1002/jcop.22689
|View full text |Cite
|
Sign up to set email alerts
|

Activities and relationships with parents as key ecological assets that encourage personal positive youth development

Abstract: Scientific literature has shown contextual factors that predict youth development, and family variables are the most important ones. In this study, we propose a model that explains the relation between family variables (relationship with parents and family activities) and Personal Positive Youth Development (assessed through Life satisfaction, Interiority, and Self‐control), across different cultures. We recruited 2867 adolescents aged 12–18 years (52% female) from three countries: Spain, Mexico, and Peru. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 70 publications
0
10
0
3
Order By: Relevance
“…Indeed, one study showed that positive affect predicted high school students’ satisfaction with family life [ 151 ]. On the other hand, other studies identified family satisfaction as a significant predictor of life satisfaction [ 170 , 171 , 172 , 173 ]. For instance, some authors [ 36 , 149 ] found that high satisfaction with family life was related to a greater frequency and intensity of affective experiences of love, affection, joy, and happiness [ 174 ].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, one study showed that positive affect predicted high school students’ satisfaction with family life [ 151 ]. On the other hand, other studies identified family satisfaction as a significant predictor of life satisfaction [ 170 , 171 , 172 , 173 ]. For instance, some authors [ 36 , 149 ] found that high satisfaction with family life was related to a greater frequency and intensity of affective experiences of love, affection, joy, and happiness [ 174 ].…”
Section: Resultsmentioning
confidence: 96%
“…Children’s and adolescents’ global happiness correlated positively with family relationships [ 12 , 90 , 91 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 ]. Positive relationships within the family strongly predicted increased subjective happiness [ 172 , 198 , 199 ] and low depressive symptoms. Children who reported more daily activities with family members reported higher levels of happiness, regardless of the type of activity (e.g., talking, playing, learning together).…”
Section: Resultsmentioning
confidence: 99%
“…Based on Five Cs PYD perspective, there is an approach focused on the flourishing of personal competencies (e.g., Balaguer, Orejudo, et al, 2020;Oliva et al, 2010;Orejudo et al, 2013Orejudo et al, , 2021. This approach shares with the Five Cs perspective their line on understanding how adolescents generate flexible and adaptive answers to the developmental tasks they daily face.…”
Section: The Personal Positive Youth Development (Ppyd) Approachmentioning
confidence: 99%
“…The personal and peripheral competencies nurture each other. Balaguer, Orejudo, and collaborators (Balaguer, Orejudo, et al, 2020;Orejudo et al, 2021) delved into these personal constructs, proposing a personal model of PYD, that is PPYD. They focus on the personal core of PYD following the mentioned classification by Oliva et al (2010).…”
Section: The Personal Positive Youth Development (Ppyd) Approachmentioning
confidence: 99%
“…Prior research has identified various indicators that promote positive development, including education attainment, strong social relationships, pro-social behavior, pro-social attitudes, and avoidance of violence and alcohol and drug use [ 19 , 20 , 21 ]. It is also clear that a positive and secure family positively correlates with life satisfaction [ 22 ]. Further, Bruner and colleagues [ 6 ] identified education involvement as a useful resource to promote positive development among Aboriginal youth in Australia.…”
Section: Introductionmentioning
confidence: 99%